Turkey : Tenth Review Under the Stand-By Arrangement-Staff Report; and News Brief on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2002)
This paper assesses Turkey's Tenth Review Under the Stand-By Arrangement (SBA). The IMF supports Turkey's economic program under an SBA covering 2000-02. The arrangement was augmented with resources under the Supplemental Reserve Facility in December 2000, and under the credit tranches in May 2001. Since the ninth review, the authorities have kept macroeconomic policies in line with the strengthened program adopted in May 2001. All performance criteria for the tenth review have been met, as have those for the eleventh review.